Toponimia, naturaleza e identidad de lugares sagrados del Geoparque Imbabura – cantón Cotacachi - Guandinango Conde, Cristhian Mauricio (2023)
In the present toponymy research, nature and cultural identity uniquely converge in the sacred sites of the Imbabura Geopark-Canton Cotacachi, forming a network of profound and symbolic meanings. Geographical names, or toponymy, are not merely descriptive labels\; they encapsulate ancestral narratives and reflect the intricate relationship between the community and its environment. These names, mostly in Kichwa, convey information about the history, function, and spirituality of these places. Additionally, sacred sites are inexorably intertwined with the surrounding nature. Waterfalls, springs, mountains, and rivers take on spiritual and cultural dimensions, being considered points of connection with the spiritual world and Mother Earth. These natural spaces, infused with significance, serve as settings for rituals, ceremonies, and traditional teachings. Ultimately, cultural identity is enriched through these sacred sites. Understanding and respecting toponymy and nature strengthen community identity, as these aspects are deeply embedded in their daily practices, beliefs, and worldview. The conservation and transmission of toponymy and the relationship with nature in cultural identity not only safeguard cultural heritage but also provide opportunities for sustainable tourism, education, and intercultural dialogue. Ultimately, the study of the intersection between toponymy, nature, and identity in the sacred sites of the Imbabura Geopark-Canton Cotacachi highlights the depth of the relationship between humans and their environment, emphasizing the importance of conserving and respecting these vital aspects of culture.